A Reconfigurable Computing System Based on a Cache-Coherent Fabric - Oliver, N.; Sharma, R. R.; Chang, S.; Chitlur, B.; Garcia, E.; Grecco, J.; Grier, A.; Ijih, N.; Yaping Liu; Marolia, P.; Mitchel, H.; Subhaschandra, S.; et al. (2011 International Conference on Reconfigurable Computing and FPGAs, 2011)
Typical reconfigurable computing systems are based on an I/O interconnect such as PCIe. This yields good bandwidth performance, but incurs significant overhead for small packet sizes, and makes the implementation of on-streaming-data applications unduly difficult. We describe an architecture based on Intel ® Quick Path Interconnect ® that addresses these concerns.